Finite Element Method Analysis of Hip-Joint Prosthesis (Hungarian Journal of Industry and Chemistry, 2011)
Damage in the joints may entail deterioration of life quality to a great extent. More than seven hundred thousand big joint (hip-, knee, etc.) prostheses are implanted annually in the world to improve the quality of life, and this number in Hungary amounts to approximately ten thousand. Currently the lifetime of the prosthesis is approximately 10 years. Unfortunately, prosthesis loosens beyond this period, thus replacement is needed. In this paper we present the geometric construction, modelling and Finite Element Analysis of the hip-joint prosthesis.